Précis of Radical Skepticism and Epistemic Intuition - Bergmann, Michael (International journal for the study of skepticism, 2023)
In this précis of Radical Skepticism and Epistemic Intuition, I highlight the main lines of argument in the book and provide an outline of each of the book’s three parts. I explain how: Part I lays out an argument for radical skepticism and objects to one of the two main ways of responding to it; Part ii presents my version of the other main way of responding to that skeptical argument (a version that relies heavily on epistemic intuition); and Part iii defends epistemic intuition (and, thereby, my response to radical skepticism) from several important objections.